Is tax funding of health care more likely to be regressive than systems based on social insurance in low- and middle-income countries? - Aurelio Mejía Mejía (Lecturas de Economía, 2013)
One of the main functions of health care systems is to collect enough revenue to finance health expenditures. This revenue can be obtained through different sources (taxes, social insurance contributions, out-of-pocket payments, donations), each of which has different implications in terms of equity. The equity implications of the different forms of revenue collection are an important component of health systems performance evaluation. The international evidence suggests that tax funded systems seem to be a more progressive health care financing mechanism than systems based on social insurance in low- and middle-income countries. However, progressivity results are sensitive to the choice of ability to pay measures and, therefore, policy makers must be aware of this fact when interpreting results of studies on health care financing.